Effect of Substrate Composition on Yield and Antioxidative Activity of Exopolysaccharides From Lactobacillus fermentum B62 - Liu Gengdian; Shu Guowei; Lei Huan; Zhang Qi; Cui Xiuxiu; Dai Chunji; Li Yilin (Acta Universitatis Cibiniensis. Series E: Food Technology, 2022)
Exopolysaccharides (EPS) can not only give food a unique texture but also has antioxidant capacities. To select the medium composition that influences the yield and antioxidative activity of EPS, Plackett–Burman (PB) design was employed to appraise the effects of carbon sources, nitrogen sources, and inorganic salts on yield and DPPH free radical scavenging (DPPH-FRS) rate of EPS in MRS medium fermented by Lactobacillus fermentum B62. The result indicated that sucrose (p<0.01), peptone (p<0.01), and KH2PO4 (p<0.001) had the most distinguishing comprehensive effects on yield and DPPH-FRS rate of EPS, and fructose also had a noticeable effect on the two factors (p<0.05, p<0.001, respectively). Additionally, glucose (p<0.05), soy protein (p<0.001), yeast extract (p<0.01), KH2PO4 (p<0.001) and Ca(H2PO4)2 (p<0.001) significantly positive affect the yield of EPS. And inulin (p<0.05), tryptone (p<0.001), beef extract powder(p<0.001), NaH2PO4 (p<0.01) and C2H3NaO2 (p<0.05) significantly positive affect the DPPH-FRS rate of EPS. Within the test ranges, sucrose, fructose, peptone and KH2PO4 all showed significant positive relativity to the yield and anti-oxidative activity of EPS.